2001
DOI: 10.1002/1521-3765(20010417)7:8<1614::aid-chem16140>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Nickel-Catalyzed Hydrocyanation of Vinylarenes by Applying Homochiral Xantphos Ligands

Abstract: New homochiral xantphos-type diphosphonite ligands with binaphthoxy substituents have been prepared and characterized by NMR spectroscopy. These ligands have been applied in the nickel-catalyzed hydrocyanation of styrene and other vinylarenes. Enantioselectivities up to 63% ee have been obtained by using 4-isobutylstyrene as a substrate. Addition of an excess of ligand strongly inhibits the hydrocyanation reaction since the bis-chelate nickel complexes formed are highly stable and catalytically inactive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
47
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(48 citation statements)
references
References 19 publications
0
47
0
1
Order By: Relevance
“…In fact, large-bite-angle diphosphine ligands with a rigid xanthene backbone give very stable and selective catalysts for the Pt-catalyzed hydroformylation of alkenes [16]. We already successfully prepared and applied chiral xanthene-based diphosphonite ligands in the nickel-catalyzed asymmetric hydrocyanation [17] and the rhodiumcatalyzed asymmetric hydroformylation [18]. Here, we report on the use of the chiral diphosphonite ligand (R,R)-XantBino ((R)-1) [19] in the Pt/Sn-catalyzed asymmetric hydroformylation of styrene (4a), 4-methylstyrene (4b), vinyl acetate (4c), and allyl acetate (4d).…”
Section: Dedicated To Professor Giambattista Consiglio On the Occasiomentioning
confidence: 99%
“…In fact, large-bite-angle diphosphine ligands with a rigid xanthene backbone give very stable and selective catalysts for the Pt-catalyzed hydroformylation of alkenes [16]. We already successfully prepared and applied chiral xanthene-based diphosphonite ligands in the nickel-catalyzed asymmetric hydrocyanation [17] and the rhodiumcatalyzed asymmetric hydroformylation [18]. Here, we report on the use of the chiral diphosphonite ligand (R,R)-XantBino ((R)-1) [19] in the Pt/Sn-catalyzed asymmetric hydroformylation of styrene (4a), 4-methylstyrene (4b), vinyl acetate (4c), and allyl acetate (4d).…”
Section: Dedicated To Professor Giambattista Consiglio On the Occasiomentioning
confidence: 99%
“…[13] We have previously reported on the use of chiral xanthene-based diphosphonites in the asymmetric hydrocyanation of vinyl arenes that showed good enantioselectivities of up to 63% for 4-isobutylstyrene. [14] We recently published on the synthesis and use of sterically constrained achiral diphosphonites L 4 in the rhodium-catalyzed hydroformylation of alkenes and showed that these systems are wellsuited for the conversion of 2-butene into n-pentanal. [15] Together with our studies on the coordination chemistry of these xanthene-derived diphosphonites towards various transition metals, [16] this prompted us to explore the potential of chiral diphosphonite 1 in various asymmetric catalytic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…), toluene, tetrazole, ∆T, 1 day erate to good yield. [14] Subsequently, the chiral binaphthyl groups were introduced to obtain the desired chiral diphosphonite. This reaction is catalyzed by tetrazole as protonation agent, which is a slight but important modification of the literature procedure.…”
mentioning
confidence: 99%
See 2 more Smart Citations